factor completely: 128x^6 - 2y^6
I can expand it to: 2(8x^3 + y^3)(8x^3 - y^3)
I know it can be expanded more but how would that go?
2(8x^3 + y^3)(8x^3 - y^3)
Hmm .... the two similar terms can be further factored like this
(2x+y)*(4x^2-2xy+y^2) ==> 8x^3 - 4x^2y + 2xy^2 + 4x^2y - 2xy^2 + y^3 ==> 8x^3 + y^3
(2x-y)*(4x^2+2xy+y^2) ==> 8x^3 + 4x^2y + 2xy^2 - 4x^2y - 2xy^2 - y^3 ==> 8x^3 - y^3
"The physicists defer only to mathematicians, and the mathematicians defer only to God ..." - Leon M. Lederman